(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research at identify the importance of e-learning in teaching mathematics and its methods from the point of view of the mathematics department teachers in the College of Basic Education. researcher prepared a questionnaire e-learning, we have produced questionnaire of the validity and the reliability, The questionnaire becomes final form is composed of (39) items divided in to(5) field(e-learning in the tasks of mathematics curriculum, e-learning in the role of mathematics teacher, e-learning in the role of student, e-learning in the tools of developing mathematics e-learning in mathematics teaching evaluation (,After that, the questionnaire was applied on the research sample consists of (70) teachers of basic education Colleges from Al-Mustansiriyah University and Maysan University, To achieve the aim of the research, use the following: statistical means, standard deviations, Independent-samples (t-test), Research results showed to The degree of importance of e-learning for the teachers of the mathematics department was on (36) items out of (39) items. The order of the fields of the questionnaire in descending order of importance are: (E-learning in the role of mathematics teacher, E-learning in the tools development mathematics, E-learning in mathematics teaching evaluation, E-learning in the role of students, E-learning in the tasks of the mathematics curriculum). There are statistically significant differences at the level of significance (0.05) in the mean the estimation of the mathematics department teachers in the degree of importance of e-learning for each field of the questionnaire due to the age variable. There are no statistically significant differences at the level of significance (0.05) in the mean the estimation of mathematics department teachers in the degree of importance of E -learning for each field of the questionnaire due to the gender variables , educational level and years of service. In the light of the results of the research , the researcher presented some recommendations and suggestions for the purpose of doing research and subsequent studies.